A Strategy-Based Framework for Accommodating Reductions in the Defense Budget - Johnson, Stuart E. (RAND Corporation, 2012)
RAND analysts posit that the ongoing pressure to reduce the federal budget deficit may result in further reductions in the Defense Department budget and suggest starting from a strategy basis in determining the reductions, prioritizing challenges, and identifying where to accept more risk. The report demonstrates this approach using three illustrative strategic directions.